Customary of CPW configuration’s in silicon RF technology targeting monolithic integration for GHz to THz frequency band - Biswas, Biswas; Karmakar, Ayan (Elsevier, 2022)
This article outlines the various configurations of co-planar waveguide (CPW) structures widely employed in silicon-RF (Si-RF) technology along with its empirical circuit modeling. Design aspects, realization techniques, mitigation strategies of commonly associated spurious modes, and finally various kinds of discontinuities in the CPW structures for Si-RF technology has been detailed in this work. Empirical modeling along with full-wave analysis of all these circuits has been carried out to decipher the actual device physics. Qualitative as well as quantitative ways have been adopted here for expressing various parasitic.
Only IISER Mohali authors are available in the record.
Keywords: Customary; configuration’s; targeting monolithic; GHz to THz frequency